Review of the genus Mansonella Faust, 1929 sensu lato (Nematoda: Onchocercidae), with descriptions of a new subgenus and a new subspecies - Bain, Odile; Mutafchiev, Yasen; Junker, Kerstin; Guerrero, Ricardo; Martin, Coralie; Lefoulon, Emilie; Uni, Shigehiko (Zootaxa, 2015)
Based on material deposited in museum collections, twelve species within Mansonella sensu lato were examined and their descriptions amended. Based on additional morphological details, the erection of the new monotypic subgenus Filyamagutia Bain & Uni for M. (F.) akitensis (Uni, 1983), and the new combination M. (Pseudolitomosa) musasabi (Yamaguti, 1941) Bain & Uni are proposed. A new subspecies, M. (Tetrapetalonema) atelensis amazonae Bain & Guerrero is described and a key to the seven subgenera of Mansonella is provided. Furthermore, the elevation of Sandnema to full genus rank comprising the two species S. digitatum (Chandler, 1929) n. comb. and S. sunci (Sandground, 1933) n. comb., is proposed. Host and geographic records for the species of Mansonella and Sandnema are included.